Solve the following linear equation.
$ m-\frac{m-1}{2}=1-\frac{m-2}{3} $.

AcademicMathematicsNCERTClass 8

Given:

$m-\frac{m-1}{2}=1-\frac{m-2}{3}$.

To do:

We have to solve the given linear equation.

Solution:

$m-\frac{m-1}{2}=1-\frac{m-2}{3}$

This implies,

$m-\frac{m-1}{2}+\frac{m-2}{3}=1$

$\frac{6(m) - 3( m-1) +2(m-2)}{6}=1$

$6m-3m+3+2m-4= 1\times6$

$5m-1= 6$

$5m=6+1$

$5m=7$

$m =\frac{7}{5}$

The value of $m$ is $\frac{7}{5}$.

raja
Updated on 10-Oct-2022 13:47:38

Advertisements